Studi Potensi Daya Tarik Wisata Sungai Gelar Desa Batuagung Sebagai Wisata Alam - Ardans, Made Meisa Putra; Sugianthara, Anak Agung Gede; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.7, No.2, Oktober 2021DO - 10.24843/JAL.2021.v07.i02.p09, 2021)
Study on the potential of gelar river tourist attractions, Batuagung Village as nature tourism. The Gelar River area is a tourist attractions that located in Batuagung Village. Gelar River planned to be developed into local tourism based on natural tourism. Local tourism is tourism whose scope is limited to certain places, namely the Jembrana district. This study aims to determine the natural resources that have the potential as natural tourism and the potential development solutions in the Gelar River so that it can be developed into sustainable nature tourism. The method used is the survey method. The data collected in the form of primary data and secondary data. The techniques applied to collect the data in current study are observation, interviews, and literature study. The interview was conducted with the management of the Gelar River Tourist Attraction and the Jembrana District Forestry and Plantation Service. Based on the results of the study, it is known that the geographical location, climate and weather, topography and landform, surface materials, water, vegetation, and fauna are natural resources that have the potential to develop the Gelar river Tourist Attraction.